2010
DOI: 10.4314/biokem.v21i2.56467
|View full text |Cite
|
Sign up to set email alerts
|

Serum Level of Antioxidant Vitamins (Vitamin A, C and E) in ,i>Plasmodium falciparum</i> Malaria Infected Children in Owerri, Eastern Nigeria

Abstract: The levels of antioxidant vitamins were estimated in Plasmodium falciparum malaria infected children. Forty-three children with P.falciparum infection were selected based on the clinical symptoms. Twenty-two apparently healthy children with no malaria parasitaemia were included as the control subjects. P.falciparum parasitaemia and serum levels of the antioxidant vitamins (vitamin A, C and E) were determined using standard procedures. It was observed that all parameters measured were significantly lower in mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…The reduction of these antioxidants in the face of malarial infection may predispose the children to free-radical attack. This finding is in agreement with previous reports 912. The low antioxidant vitamin levels observed in this study may be as a result of increased utilization of the host’s plasma antioxidants by the malaria parasite to counteract the malarial infection-associated oxidative damages 26.…”
Section: Discussionsupporting
confidence: 94%
“…The reduction of these antioxidants in the face of malarial infection may predispose the children to free-radical attack. This finding is in agreement with previous reports 912. The low antioxidant vitamin levels observed in this study may be as a result of increased utilization of the host’s plasma antioxidants by the malaria parasite to counteract the malarial infection-associated oxidative damages 26.…”
Section: Discussionsupporting
confidence: 94%
“…Treatment of malaria in Nigeria particularly in this era of drug resistance, is expensive for a majority of the sufferers who might barely afford the antimalarial drug designated as first line and will not see the need to buy any prescribed antioxidant as they are added expenses. Ekeanyanwu et al .,[ 24 ] and Aghedo et al .,[ 25 ] showed from their studies that the antioxidant levels in plasmodium-parasitized children in the North-West of Nigeria were low and that the more severe the malarial infection, the lower the antioxidant level and the packed cell volume. They recommend that malaria-parasitized children, particularly those in the North-West of Nigeria, be placed routinely on antioxidant vitamins to manage the micronutrient deficiencies as was seen in the children.…”
Section: Discussionmentioning
confidence: 99%
“…They recommend that malaria-parasitized children, particularly those in the North-West of Nigeria, be placed routinely on antioxidant vitamins to manage the micronutrient deficiencies as was seen in the children. The non-usage of antioxidants to manage micronutrient deficiencies is not limited to one geographical region according to an earlier report by Ekeanyanwu et al .,[ 24 ] from studies carried out in Southeastern Nigeria. Therefore, there will be potential benefit of antioxidant supplementation with the use of CQ or other antimalarials.…”
Section: Discussionmentioning
confidence: 99%
“…In severe malaria, there is parasite induced oxidative stress which depletes some components of the antioxidant system; this leads to increased oxidation of biomolecules such as protein, thus causing an elevation in serum PCO level [50] with a decrease in the serum antioxidant (SOD), thus overwhelming the first line enzymic antioxidant defense in an attempt by the host to offset the effect of the increasing oxidative stress [51][52]. This study revealed normal serum bicarbonate level compared to control and it followed no regular pattern with increase in parasite density (Tables 1 and 2).…”
Section: Discussionmentioning
confidence: 99%